Ambient Space - Thomas, Paul (John Curtin Gallery, 2003)
Ambiantspace is a video work exploring the effects of emergent media on the imagination through the translucent layering of imagery. The work presents spatial paradigms as examples of significant spaces. Just as perspective changed our perception last century so new technologies are now reshaping our presence in world. The work documents a variety of residual spaces not as material representation of the new cyberspace but as significant symbols that have been composited to deconstruct traditional perspectival rhetoric. The work introduces a mimetic body that is created out of captured media fragments through a process of merging residual spaces. The 'Ambiantspace' project is not aimed at using the perspectival paradigm as a platform to present new media image, or understanding of itself. Rather it proposes a new paradigm that allows for the possible objectifications of spatial reconfigurations of perception occurring with new technologies, which is the principle area of research in this project. This work took part of the footage from Ambiance and reworked it into one hundred and twenty short video clips. Each one of these clips was related to a piece of text again from the Ambiance work. The one hundred and twenty video clips where then selected into twelve categories which I have called chapters. Each of the chapters lasts for 10 minutes so the whole work is two hours in length. I took the sound from the video, which I then mixed, together in 5:1 surround sound to complement the experience of the space.